2005
DOI: 10.1177/1363461505058920
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Treatment Choices by South and East Asian Women with Serious Mental Illness

Abstract: The purpose of this qualitative study is to investigate how South and East Asian immigrant women who have diagnoses of serious mental illness make treatment choices in relation to spirituality and to explore how gender, cultural beliefs, and spirituality intersect with the process of choice. The findings reveal that the process of spiritual choice includes three interrelated phases: (1) identifying contributing factors, (2) exploring spiritual resources and strategies, and (3) living with the choices. Variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…These findings concur with reports by Chiu et al [8] and Jacob et al [12] that the tendency to hide illness often resulted in GPs failing to detect mental illness, and many patients either being undiagnosed or misdiagnosed. Jacob et al [12] also found that doctors often believe that mental illness is managed within the family in Asian communities.…”
Section: Gps' Understanding Of Mental Illness and Its Causesupporting
confidence: 90%
See 2 more Smart Citations
“…These findings concur with reports by Chiu et al [8] and Jacob et al [12] that the tendency to hide illness often resulted in GPs failing to detect mental illness, and many patients either being undiagnosed or misdiagnosed. Jacob et al [12] also found that doctors often believe that mental illness is managed within the family in Asian communities.…”
Section: Gps' Understanding Of Mental Illness and Its Causesupporting
confidence: 90%
“…Participants elaborated on the above, stating that family issues have a serious impact on patients' wellbeing in the Lenasia community (reflecting financial pressures on married couples, both of whom often need to work, limited family time, marital conflicts, or changes in marital status such as divorce or death of a spouse). This concurs with Chiu et al 's [8] finding that Canadian Asian women reported becoming mentally ill due to their extremely stressful lifestyles when they were expected to work, take care of children and do household chores. Marital conflict and relationships with inlaws were exacerbating factors.…”
Section: Gps' Understanding Of Mental Illness and Its Causesupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies further suggested that stigma in Asian culture is more severe than that in Western culture (Whaley, 1997;Lauber and Rössler, 2007), due to the group-centered nature which is common among Asian populations (Chong et al, 2007;Papadopoulos, 2009;Abdullah and Brown, 2011). In addition, the patterns of stigma vary throughout Asia (Yamamoto et al, 1996;Ng, 1997;Kurihara et al, 2000;Yamada et al, 2001;Chiu et al, 2005) and even between East Asian countries of similar cultures (Kumakura et al, 1992;Hanzawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Social and cognitive disability in patients with primary psychotic disorders may increase their vulnerability to advertisements of the purported therapeutic benefits of CAM. Other factors such as gender and underlying belief systems are also likely to contribute to the use of CAM (Chiu et al, 2005). We therefore conducted a survey of ambulatory patients with schizophrenia and related primary psychotic disorders followed at an inner city psychiatric hospital in Toronto to determine the prevalence and attitudes toward the safety and benefits of CAM.…”
Section: Introductionmentioning
confidence: 99%